Development and experimental validation of discovery learning-based worksheets integrating cultural context to enhance students’ mathematical literacy and self-regulated learning - Windhy Wijayanti; Fitrianto Eko Subekti (CV. FOUNDAE, 2026)
Background: Mathematics learning often relies on conventional teaching materials that are less effective in supporting students’ conceptual understanding, particularly in abstract topics such as curved surface geometry. This limitation contributes to students’ learning difficulties and low engagement, as instructional media rarely integrate meaningful cultural contexts that can connect mathematical concepts to students’ real-life experiences. Aims: This study aims to develop Discovery Learning-based student worksheets (LKPD) integrated with the Hadroh cultural context to enhance students’ conceptual understanding in mathematics learning. Method: This study employed a research and development design using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The participants were Grade IX students selected through purposive sampling. Data were collected using expert validation sheets, student response questionnaires, and conceptual understanding tests. Data analysis was conducted based on validity, practicality, and effectiveness criteria. Results: The findings indicated that the developed LKPD achieved a high level of validity, with an average score of 4.39 categorized as very valid. The practicality test showed a percentage of 84%, indicating that the worksheets were highly practical for classroom use. Furthermore, the effectiveness test revealed that students who used the developed LKPD demonstrated better conceptual understanding compared to those who used conventional teaching materials. Conclusion: The Discovery Learning-based LKPD integrated with the Hadroh cultural context is valid, practical, and effective in improving students’ conceptual understanding, providing an alternative instructional material that supports more meaningful and student-centered mathematics learning.